(untitled) (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2014)
This paper aims to critically analyse the testimonies concerning Athenian impiety trials of the classical period. First, it reaffirms the arguments that some of them must have been an invention of Hellenistic and later authors. Second, it presents a likely political background behind the historical cases. Third, it discusses a number of legal issues, along with new arguments concerning the procedures employed. Finally, it examines some less well-known material from the fourth century BCE. Overall, it seeks to provide a possibly coherent and comprehensive framework of Athenian impiety trials based on their shared characteristics.